Tantra in Bengal : a study in its origin, development and influence - Banerji, S. C (New Delhi : Manohar Publishers, 1992)
Art, Culture and History
2006\04\02
Keywords: Religious beliefs; Religious doctrine; Hinduism; Culture; India%Bangladesh; Buddhism; Brahman